MODEL PENILAIAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI MTs SWASTA KABUPATEN ROKAN HULU - Widodo, Widodo (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
Affective domain assessment at the spiritual level is one type of assessment in Islamic Religious Education learning. However, the problems found in the field, Islamic Religious Education teachers tend to ignore affective assessments at the spiritual level and focus more learning on cognitive completion alone. The purpose of this study is 1) To develop an assessment model of learning outcomes of Islamic Religious Education in Private Madrasah Tsanawiyah Rokan Hulu Regency which has been carried out so far. 2) To develop an ideal Model of Learning Outcomes of Islamic Religious Education in Tsanawiyah Private Madrasah in Rokan Hulu Regency. This type of research uses the development (Research and Development). The results of this study are 1) The assessment model of Islamic Religious Education learning outcomes in Private MTs is declared invalid. and 2) The ideal model of assessment of learning outcomes of Islamic Education in Private Madrasah Tsanawiyah in Rokan Hulu Regency, the writer does through the process of research and development (Research and Development). After the formulation of a model for evaluating Islamic religious education learning outcomes is formed, the model for evaluating Islamic religious education learning outcomes is more effective and efficient.